AGRESIVITAS PAJAK YANG DIPENGARUHI OLEH KOMPENSASI EKSEKUTIF, KONEKSI POLITIK, PERTUMBUHAN PENJUALAN, LEVERAGE DAN PROFITABILITAS - Ernie Riswandari; Kevin Bagaskara (Jurnal Akuntansi, 2020)
This research aims to prove that tax aggressiveness is influenced by executive compensation, political connections, sales growth, leverage, and profitability. The annual reports of BUMN & BUMS companies in the non-financial sector are secondary data used in this study and by using the purposive sampling method in selecting the sample. The method of analysis used in this study is multiple linear regression. The result shows that the executive compensation variable has a positive effect on tax aggressiveness. Political connection variables, sales growth, and leverage have a negative effect on tax aggressiveness, while the profitability variable has no effect on tax aggressiveness. Keywords: Executive compensation, political connection, sales growth, leverage, profitability, tax aggressiveness